Human rights in diverse education contexts - Beckmann, Johan (NWU Education and Human Rights in Diversity Series, 2019)
The focus of this publication is on answering the central research question: How can Human Rights be advanced with regard to different kinds of diversities, and in different educational settings? The publication pays special attention to the advancement of human rights in a variety of education-related contexts, in keeping with human rights as a declared national priority for both society at large and the education system. One strategic priority of the Faculty of Education is research based on market requirements and needs. This book strives towards meeting this expectation by directly aiming at building human rights and social justice in the South African society, public schools and higher education institutions. Adjudication in the education context of the constitutional values of dignity, equality and freedom focusses regularly on learners. The book highlights the value of education for full-fledged citizenship by delineating what schooling should entail to inspire learners towards both claiming equal freedoms and rights and taking accountability for the responsibilities attached to citizenship.